Evaluation of antibiotic use in patients treated for uncomplicated malaria in the city of Boma, Democratic Republic of the Congo - KILARA KAPENE, Tarcisse; Pholo, Jean Paul M.; Mpiempie, Thérèse N.; Ngale, Mireille; Divengi, Jean Paul N.; Kondani, Mamie A.; Gimbindu, Tony. A.; Velela, Percy K.; Ilenga, Willems M.; Balu, Constant. M.; Woto, Isaac T.; Bongenya, Berry I.; et al. (Orapuh Journal, 2025)
IntroductionMalaria remains one of the leading causes of morbidity and mortality in sub-Saharan Africa. In the Democratic Republic of the Congo (DRC), it accounts for approximately 12% of morbidity, primarily affecting children under five. Following the 2015 World Health Organization (WHO) guidelines, artemisinin-based combination therapy (ACT) is recommended.PurposeTo assess the use of antibiotics co-administered with antimalarial drugs in the treatment of uncomplicated malaria in Boma.MethodsThis descriptive, cross-sectional study retrospectively reviewed records of patients with uncomplicated malaria registered between January and June 2022 to evaluate antibiotic co-prescription with antimalarials. Data collection occurred in July 2022. The study was conducted in Boma, at the Boma Red Cross Clinic and the Boma/MABAKU inter-diocesan hospital. A non-probability convenience sample of 100 patient files was examined. All patients included had uncomplicated malaria and received antibiotic therapy. Descriptive statistics and 95% confidence intervals (CIs) were calculated using Stata 12.0.ResultsChildren aged 0–5 years comprised 36% of patients. Males accounted for 60% (95% CI: 50–69%), and females for 40% (95% CI: 31–50%); no significant sex difference was observed (p = 0.12). Before treatment, 80% of patients had a positive thick blood smear, 15% were treated without a definitive diagnosis, and only 5% had blood cultures performed. LA was the most prescribed ACT (90%). Among antibiotics, ceftriaxone was the most frequently prescribed (27%). Overall, 83% received antibiotics not aligned with guidelines, and 12% received quinine combined with doxycycline or clindamycin.ConclusionThe findings indicate excessive and occasionally inappropriate antibiotic use in managing uncomplicated malaria in Boma health facilities. These results underscore the need for stronger adherence to National Malaria Control Program (PNLP) guidelines and enhanced antibiotic stewardship training for prescribers.